Subacute sclerosing panencephalitis: detection of measles virus RNA in appendix lymphoid tissue before clinical signs. Issue 6546 (30th August 1986) - Fournier, J G; Lebon, P; Bouteille, M; Goutieres, F; Rozenblatt, S
Abstract : An appendix removed 15 days before onset of symptoms of subacute sclerosing panencephalitis was examined retrospectively for measles virus ribonucleic acid (RNA). Tissue sections hybridised in situ to a cloned measles virus probe of deoxyribonucleic acid specific for nucleocapsid protein showed that many cells of the lymphoid tissue contained measles virus RNA. In contrast, only a few infected lymphoid cells were detected in three out of six seropositive controls and none in three seronegative infants. A widespread chronic viral infection of the immune system, established after measles, may promote or even initiate nerve cell infection in subacute sclerosing panencephalitis.